1974
DOI: 10.1002/ijc.2910130202
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and isolation of immunologically active glycopeptides from carcinoembryonic antigen (CEA)

Abstract: In order to determine the structure of the tumor-specific immunodominant group of the carcinoembryonic antigen ( C E A ) of human gastro-intestinal tumors, immunologically active fragments from this glycoprotein were prepared by partial enzymatic hydrolysis using the proteolytic enzyme nagase. The fragments were purified by sequential molecular sieve, adsorption and ion exchange chromatography, and were analysed for carbohydrate and amino-acid composition by gas-liquid chromatography. The antigenic activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
1
1

Year Published

1974
1974
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 15 publications
0
16
1
1
Order By: Relevance
“…Evidence for the involvement of 2-acetamido-2-deoxyglucose in the immunodominant grouping has been presented by Banjo et al (1972) and is well supported by further work from the same laboratories (Banjo et al, 1974). In addition, Watanabe and Hakomori (1973) have shown that purified glycosphingolipids from tumour tissue or erythrocytes give a strong precipitin reaction with wheat germ lectin and with anti-CEA.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Evidence for the involvement of 2-acetamido-2-deoxyglucose in the immunodominant grouping has been presented by Banjo et al (1972) and is well supported by further work from the same laboratories (Banjo et al, 1974). In addition, Watanabe and Hakomori (1973) have shown that purified glycosphingolipids from tumour tissue or erythrocytes give a strong precipitin reaction with wheat germ lectin and with anti-CEA.…”
mentioning
confidence: 75%
“…In addition, Watanabe and Hakomori (1973) have shown that purified glycosphingolipids from tumour tissue or erythrocytes give a strong precipitin reaction with wheat germ lectin and with anti-CEA. It is known that sialic acid does not form part of the immunological determinant (Banjo et al, 1972;Coligan et al, 1973), nor, according to recent work on the treatment of CEA with periodate, does fucose (see Terry et al, 1974). Recently, Neveu et al (1975) proposed that CEA and the " nonspecific crossreacting antigen ", NCA, have common antigenic determinants on both the carbohydrate and polypeptide parts of the molecule, while Hammarstrom et al (1975) conclude, tentatively, that the carbohydrate moiety of CEA does not contain the tumour associated determinant(s).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It cannot be excluded that this is due to similarity between the protein moieties of molecules but it seems more probable that the glucidic moieties were involved. These moieties play an important role in the reactivity of CEA (and logically NCA) with specific antibody, as judged by the work of Banjo et al (1974); these authors demonstrated that acetylglucosamine and asparagine played an important role in the main antigenic determinant of CEA.…”
Section: Discussionmentioning
confidence: 99%
“…No other carbohydrates were detected. In a subsequent report, digestion of CEA with the proteolytic enzyme nagase resulted in immunologically active glycopeptides (Banjo et al, 1974). N-acetyl D-glucosamine was present on all the fragments which were antigenic.…”
mentioning
confidence: 90%